2019
DOI: 10.1108/jaee-04-2018-0035
|View full text |Cite
|
Sign up to set email alerts
|

Personal and moral intensity determinants of ethical decision-making

Abstract: Purpose The purpose of this paper is to examine the influence of personal and moral intensity variables on specific processes, namely, ethical recognition, ethical judgment and ethical intention, involved in the ethical decision making (EDM) of accounting professionals. Design/methodology/approach A structured questionnaire containing four vignettes of ethical dilemmas is used in the paper to obtain data from 329 accounting professionals. The data are analyzed using Pearson correlation matrix, independent sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 80 publications
4
47
0
2
Order By: Relevance
“…Nasution and Ostermark (2020) did not find age, gender and education to be influencing ethical judgements of auditors in Indonesia. Similar observations were reported by Oboh (2019), where age and gender did not significantly influence ethical judgements of accounting professionals in Nigeria. These findings perhaps suggest that workplace demand or pressures may override personal characteristics or values once an individual enters the professional environment.…”
Section: Literature Review and Hypotheses Developmentsupporting
confidence: 86%
See 2 more Smart Citations
“…Nasution and Ostermark (2020) did not find age, gender and education to be influencing ethical judgements of auditors in Indonesia. Similar observations were reported by Oboh (2019), where age and gender did not significantly influence ethical judgements of accounting professionals in Nigeria. These findings perhaps suggest that workplace demand or pressures may override personal characteristics or values once an individual enters the professional environment.…”
Section: Literature Review and Hypotheses Developmentsupporting
confidence: 86%
“…However, there have also been studies that found no association between age and ethical judgements (e.g. Forte, 2004;Nguyen et al, 2008;Nasution and Ostermark, 2020;Oboh, 2019). In view of the prior studies, which generally found evidence consistent with the theory of moral development, the following hypothesis is proposed: H2.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 96%
See 1 more Smart Citation
“…This is because of rising incidences of corporate financial scandals, economic crimes, tax evasions and theft of public funds incited by questionable accounting practices in organisations across many countries (Koumbiadis, 2014; International Ethics Standards Board for Accountants [IESBA], 2015; Byrne, 2016; Kirtley and Choudhury, 2016). While the issue of ethics in the accounting profession is not at all new (Koumbiadis, 2014), recurring news headlines of questionable accounting practices have heightened global concern for the issue of moral development and its role in the ethical decision-making (EDM) process of accountants (Sikka, 2009; Akpata, 2014; Herbert et al , 2016; Musbah et al , 2016; Oboh and Ajibolade, 2018). There is a renewed call for further investigation into the moral orientation, professionalism and EDM processes of accountants and the role of professional accounting bodies in their moral development, especially in developing countries (Nathan, 2015; Musbah et al , 2016; Oboh, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For example, questionable accounting practices have contributed to making some developing countries’ economic growth projections and diversifications not to yield any substantial development and reduction in the level of poverty (Central Intelligence Agency [CIA], 2017; Transparency International, 2017). Also, advances in globalisation, bilateral and multilateral trade deals, adoption of international financial reporting standards, internationalisation of indigenous accounting firms and increased investment opportunities have mounted pressures on professional accounting bodies and regulators globally to be more proactive in promoting ethical accounting practices among accountants (Bakre, 2007; Adeyeye et al , 2010; Oboh and Ajibolade, 2018).…”
Section: Introductionmentioning
confidence: 99%